Improved photo-fermentative hydrogen production by biofilm reactor with optimizing carriers and acetate concentration. (27th September 2019) - Wen, Hanquan; Cao, Guangli; Xie, Guojun; Xing, Defeng; Yin, Tianming; Ren, Nanqi; Liu, Bingfeng
Abstract: To enhance photo-fermentative hydrogen production (PFHP), biofilm reactor (BR) was employed as an ideal strategy with optimization on key factors of acetate concentration and carriers in this work. Optimal conditions for hydrogen production were acetate concentration of 4 g/L and carriers (silicon sheet) of 10 cm × 1 cm at amount of 1 piece. Biofilm formed on silicon sheet strongly improved hydrogen production compared with control reactor (CR). Cumulative hydrogen volume was enhanced about 20% from 2850 ± 130 mL/L of CR to 3349 ± 153 mL/L of BR and hydrogen yield was increased 20% from 2.61 ± 0.13 mol H2 /mol acetate of CR to 3.06 ± 0.15 mol H2 /mol acetate of BR at 4 g/L acetate. Protein and deoxyribonucleic acid (DNA) were important components to form the biofilm and they occupied 90% of extracellular polymeric substances (EPS). In particular, DNA, nearly 50% content of EPS, likely indicated a substantial contribution to biofilm formation and bacterial communication. Moreover, it suggested biofilm could regulate free cells to decline EPS secretion for improved hydrogen production. This work indicates BR could be a promising and economic strategy to enhance hydrogen production by photo-fermentation. Highlights: Key factors of acetate concentration and carriers are optimized for biofilm reactor performance. Hydrogen production is positively correlated to the valid carrier. Biofilm bacteria regulate bioactivity and EPS secretion of total cells in the biofilm reactor. Free cells in the biofilm reactor secret less EPS for enhanced hydrogen production. Protein and DNA are important components of EPS and DNA shows a pivotal role for biofilm formation and communication.